Effect of scale of operation on heap leaching performance - Van Staden, Petrus Johannes (Department of Chemical Engineering, 2019)
The extent to which differences in bulk density and in irrigation geometry contribute towards the differences observed in leaching performance between laboratory-scale columns versus commercial-scale heaps was investigated. Furthermore, the contributions of segregation and stratification, which are absent from columns but unavoidable in heaps, were also investigated. Four case studies provided data whereby the column and heap leaching of the respective sample materials could be directly compared. The first involved gold-bearing ore, the second gold-bearing sand, a third was conducted on oxide-copper ore and the fourth case study was performed on sulphidic copper ore. The first case study was published by others, while the other three were conducted by the author himself. Furthermore, custom-designed boxes were constructed whereby the segregation and stratification of ore could be simulated. Tests were performed to observe the leaching performance of segregated and stratified ore samples, compared to unsegregated and unstratified ore samples. The leaching characteristics of each case was quantified in terms of the parameters of a mathematical model, based on dual-porosity hydrology and diffusion with chemical reaction, which provided optimised fits to the experimental data. Furthermore, fundamental relations were derived for the impact that changes in bulk density and changes in drip-irrigation spacing are theoretically expected to have on the same model parameters. These relations were tested against the actual trends observed in the model parameters that best fitted the data of the four case studies and of the segregation/stratification experiments. It was found that the diffusional distance, which places a mass-transfer limitation on the over-all rate of leaching, can be governed by either the ore bulk density, or by the irrigation dripper spacing. The relations derived under this study can be used to estimate the maximum dripper spacing that can be permitted to prevent dripper spacing from becoming the rate-limiting parameter. Estimates of the impact of dripper spacing on the ultimate extent of extraction are also provided. However, neither segregation nor stratification exhibited significant or reproducible effects on leaching kinetics. These findings can place the drafting of heap leaching design parameters on a more fundamental footing.